PENGARUH QUALITY OF WORK LIFE, MOTIVASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA GARMENT MIANA GIANYAR - Ni Kadek Trisnawati; I Gst Ngurah Bagus Gunadi; Agus Wahyudi Salasa Gama (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
This research was conducted based on the research gap and differences in focus on quality of work life, motivation, and compensation on employee performance. In addition, there are also research problems on compensation that are not good within the company. This research was conducted at Garment Miana Gianyar with a sample of 30 respondents who were taken using a saturated census. All data obtained from the distribution of questionnaires is feasible to use, then analyzed using multiple linear regression, hypothesis testing (t test and f test). The results of this study indicate that the variables: (1) quality of work life has a positive and significant effect on employee performance, (2) motivation has a positive and significant effect on employee performance, (3) compensation has a positive and significant effect on employee performance.